Modern Transport Telematics 11th International Conference on Transport Systems Telematics, TST 2011, Katowice-Ustroń, Poland, October 19-22, 2011. Selected Papers - Mikulski, Jerzy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book constitutes the proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems, SSS 2011, held in Grenoble, France, in October 2011. The 29 papers presented were carefully reviewed and selected from 79 submissions. They cover the following areas: ad-hoc, sensor, and peer-to-peer networks; safety and verification; security; self-organizing and autonomic systems; and self-stabilization.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Information Systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems